Step
*
1
1
of Lemma
member-pcs-mon-vars
.....assertion..... 
1. X1 : iPolynomial() List
2. X2 : iPolynomial() List
3. vs : ℤ List
⊢ ∀vs:ℤ List
    ((vs ∈ accumulate (with value vs and list item p):
            polynomial-mon-vars(vs;p)
           over list:
             X1
           with starting value:
            [[]]))
    
⇐⇒ (vs = [] ∈ (ℤ List)) ∨ (∃p∈X1. (∃m∈p. vs = (snd(m)) ∈ (ℤ List))))
BY
{ Assert ⌜∀L:ℤ List List. ∀vs:ℤ List.
            ((vs ∈ accumulate (with value vs and list item p):
                    polynomial-mon-vars(vs;p)
                   over list:
                     X1
                   with starting value:
                    L))
            
⇐⇒ (vs ∈ L) ∨ (∃p∈X1. (∃m∈p. vs = (snd(m)) ∈ (ℤ List))))⌝⋅ }
1
.....assertion..... 
1. X1 : iPolynomial() List
2. X2 : iPolynomial() List
3. vs : ℤ List
⊢ ∀L:ℤ List List. ∀vs:ℤ List.
    ((vs ∈ accumulate (with value vs and list item p):
            polynomial-mon-vars(vs;p)
           over list:
             X1
           with starting value:
            L))
    
⇐⇒ (vs ∈ L) ∨ (∃p∈X1. (∃m∈p. vs = (snd(m)) ∈ (ℤ List))))
2
1. X1 : iPolynomial() List
2. X2 : iPolynomial() List
3. vs : ℤ List
4. ∀L:ℤ List List. ∀vs:ℤ List.
     ((vs ∈ accumulate (with value vs and list item p):
             polynomial-mon-vars(vs;p)
            over list:
              X1
            with starting value:
             L))
     
⇐⇒ (vs ∈ L) ∨ (∃p∈X1. (∃m∈p. vs = (snd(m)) ∈ (ℤ List))))
⊢ ∀vs:ℤ List
    ((vs ∈ accumulate (with value vs and list item p):
            polynomial-mon-vars(vs;p)
           over list:
             X1
           with starting value:
            [[]]))
    
⇐⇒ (vs = [] ∈ (ℤ List)) ∨ (∃p∈X1. (∃m∈p. vs = (snd(m)) ∈ (ℤ List))))
Latex:
Latex:
.....assertion..... 
1.  X1  :  iPolynomial()  List
2.  X2  :  iPolynomial()  List
3.  vs  :  \mBbbZ{}  List
\mvdash{}  \mforall{}vs:\mBbbZ{}  List
        ((vs  \mmember{}  accumulate  (with  value  vs  and  list  item  p):
                        polynomial-mon-vars(vs;p)
                      over  list:
                          X1
                      with  starting  value:
                        [[]]))
        \mLeftarrow{}{}\mRightarrow{}  (vs  =  [])  \mvee{}  (\mexists{}p\mmember{}X1.  (\mexists{}m\mmember{}p.  vs  =  (snd(m)))))
By
Latex:
Assert  \mkleeneopen{}\mforall{}L:\mBbbZ{}  List  List.  \mforall{}vs:\mBbbZ{}  List.
                    ((vs  \mmember{}  accumulate  (with  value  vs  and  list  item  p):
                                    polynomial-mon-vars(vs;p)
                                  over  list:
                                      X1
                                  with  starting  value:
                                    L))
                    \mLeftarrow{}{}\mRightarrow{}  (vs  \mmember{}  L)  \mvee{}  (\mexists{}p\mmember{}X1.  (\mexists{}m\mmember{}p.  vs  =  (snd(m)))))\mkleeneclose{}\mcdot{}
Home
Index